THE ROLE OF TRANSPARENCY ON THE INTENTION TO DONATE MONEY TO CHARITABLE ORGANIZATIONS: A COMBINATION OF MULTIPLE CORRESPONDENCE ANALYSIS AND CONJOINT ANALYSIS - Nguyễn Văn Anh; Nguyễn Thị Phương Thảo; Kim Sung Ho (Tạp chí Khoa học Đại học Đà Lạt)
This study empirically investigated the effects of levels of attributes of charitable organizations (COs) on potential donor's intention to donate to COs by using conjoint analysis combine with multi correspondence analysis (MCA). The current study was carried out by employing questionnaire survey method. A sample of 181 respondents participated in the study. Based on previous studies, we selected four attributes which compose COs. These are: (1) Reputation (well-known/not well-known); (2) Types of activities (wildlife charity/environmental charity/humanitarian charity); (3) Benefits offered to donors (invitations to special charity gala and events/fiscal incentives/high personal recognition), and transparency (high/low). The findings of the study are as follows: (1) The most important attribute is transparency, followed by the types of activities, and benefits offered to donors. The reputation of COs turns out to be least important; (2) High transparency and COs activities of humanitarian charity have the biggest impact on the intention of donating. Managerial implications, limitations and direction for future research are discussed.